Optimization of cell density and LPS concentration for the evaluation of nitric oxide production on BV-2 cells in a Griess assay - Hosseini, Nasim Karimi; Jose, Shinsmon; Vidyadaran, Sharmili; Amin Nordin, Syafinaz (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Production of nitric oxide (NO) is one of the main responses elicited by a variety of immune cells such as macrophages (e.g. microglia, resident macrophages of brain), during inflammation. Evaluation of NO levels in the inflammatory milieu is considered important to the understanding of the intensity of an immune response; and has been performed using different methods including the Griess assay. To assay NO in culture, an appropriate number of cells are stimulated into an inflammatory phenotype. Common stimuli include lipopolysaccharide (LPS), IFN-γ and TNF-α. However, overt stimulation could cause cell cytotoxicity therefore an ideal concentration of LPS should be used. Objective: To set-up a model of BV-2 cell activation that allows the assay of detectable levels of NO. Optimization of BV-2 microglia cell density and LPS concentrations after stimulation by bacterial lipopolysaccharide (LPS) for the Griess assay is demonstrated in this study. Methods:BV-2 microglia were cultured at different cell densities, and treated with LPS at three concentrations (1, 5, 10 μg/ml). NO production in culture supernatants were then measured at 18, 24, 48 and 72 hours. Moreover, methyl tetrazolium assay (MTT) was also performed to ensure that NO measurement is performed at no-cytotoxic concentrations of LPS. Results and Conclusions: NO production follows a temporal pattern. The density of 25000 cells/well was the ideal seeding density for NO evaluation in BV-2 cells. BV-2 stimulation by LPS is dose dependent, and NO levels are increased proportional to the LPS concentration up to 1.0μg/ml, whereas the higher LPS concentrations are associated with decreased cell viability may be caused by the high toxic levels of LPS or NO. Although Griess assay has been commonly used by the scientists, however, optimization of its parameters on BV-2 cells will be useful for the experiments which will be performed on this particular cell line. The optimized pattern of Griess assay on BV-2 cells was achieved in this study, hence easier and more practical for the future scientists to perform Griess assay on BV-2 cells.